The level of myeloid derived-suppressor cells in peripheral blood of patients with prostate cancerafter various types of therapy - Siemińska, Izabela; Rychlicka-Buniowska, Edyta; Jaszczyński, Janusz; Palaczyński, Mikołaj; Bukowska-Strakova, Karolina; Ryś, Janusz; Dumański, Jan; Siedlar, Maciej; Baran, Jarosław (Polish Journal of Pathology, 2020)
Prostate cancer is one of the most frequent cancers in men. Although several treatment options exist, their clinical effectiveness is still not satisfactory. One the possible reason of such situation might be the presence of myeloid-derived suppressor cells (MDSC) and their pro-tumorigenic activity. MDSC possess immunosuppressive ability and in many studies were shown to support tumor development and progression. In this study we addressed the question whether commonly used therapies of prostate cancer affect the level of MDSC populations in the patients’ blood. We compared the level of granulocytic (Gr-MDSC), monocytic (Mo-MDSC) and early stage MDSC (eMDSC) in the blood of patients at different clinical stage and different tumor grading scores, who underwent either surgery or hormonal therapy alone or were given a combined treatment, including e.g. radiotherapy. The obtained results showed that the level of Gr-MDSC was significantly lower in all treated patients comparing to untreated group. On the other hand, surgery or hormonal therapy alone did not affect the level of Mo-MDSC. These results were independent of the PSA level, the tumor grading and clinical stage of the patients. In conclusion, we suggest that Mo-MDSC should be considered as a potential therapy target in the course of prostate cancer treatment to enhance its anti-tumor effectiveness.